Connection between right-to-left shunt and photosensitivity: a community-based cross-sectional study - Dong, Bosi; Ji, Shuming; Li, Yajiao; Li, Hua; Yang, Ruiqi; Yang, Na; Liu, Zhu; Zhu, Chenxing; Wang, Hui; Tang, Yusha; Peng, Anjiao; Chen, Lei (Frontiers in Neurology, 2023)
Background Hypersensitivity to light is a common symptom associated with dysfunction of the occipital region. Earlier studies also suggested that clinically significant right-to-left shunt (RLS) could increase occipital cortical excitability associated with the occurrence of migraine. The aim of this study was to investigate the relationship between RLS and photosensitivity. Methods This cross-sectional observational study included the residents aged 18–55 years living in the Mianzhu community between November 2021 and October 2022. Photosensitivity was evaluated using the Photosensitivity Assessment Questionnaire along with baseline clinical data through face-to-face interviews. After the interviews, contrast-transthoracic echocardiography (cTTE) was performed to detect RLS. Inverse probability weighting (IPW) was used to reduce selection bias. Photosensitivity score was compared between individuals with and without significant RLS using multivariable linear regression based on IPW. Results A total of 829 participants containing 759 healthy controls and 70 migraineurs were finally included in the analysis. Multivariable linear regression analysis showed that migraine (β = 0.422; 95% CI: 0.086–0.759; p = 0.014) and clinically significant RLS (β = 1.115; 95% CI: 0.760–1.470; p < 0.001) were related to higher photosensitivity score. Subgroup analysis revealed that clinically significant RLS had a positive effect on hypersensitivity to light in the healthy population (β = 0.763; 95% CI: 0.332–1.195; p < 0.001) or migraineurs (β = 1.459; 95% CI: 0.271–2.647; p = 0.010). There was also a significant interaction between RLS and migraine for the association with photophobia (pinteraction = 0.009). Conclusion RLS is associated with photosensitivity independently and might exacerbate photophobia in migraineurs. Future studies with RLS closure are needed to validate the findings. Trial registration This study was registered at the Chinese Clinical Trial Register, Natural Population Cohort Study of West China Hospital of Sichuan University, ID: ChiCTR1900024623, URL: https://www.chictr.org.cn/showproj.html?proj=40590.